Solvent‐, Cation‐ and Anion‐Induced Structure Variations in Manganese‐Based TCNQF4 Complexes: Synthesis, Crystal Structures, Electrochemistry and Their Catalytic Properties1. Issue 1 (12th December 2017) - Lu, Jinzhen; Abrahams, Brendan F.; Elliott, Robert W.; Robson, Richard; Bond, Alan M.; Martin, Lisandra L.
Abstract: The reaction of Mn(BF4 )2 ⋅ x  H2 O with (Pr4 N)2 TCNQF4 (TCNQF4 =2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane) in a mixture of CH3 OH/CH2 Cl2 gives a 2:3 stoichiometric complex of (Pr4 N)2 [Mn2 (TCNQF4 )3 (CH3 OH)2 ] (1 ). If the solvent system used for the crystallisation of1 is changed to CH3 OH/DMF, then a different product, [Mn(TCNQF4 )(DMF)2 ]⋅ (CH3 OH)2 (2 ), is obtained. The use of Li2 TCNQF4 instead of (Pr4 N)2 TCNQF4 leads to the generation of [Mn2 (TCNQF4 )2 (DMF)4 ]⋅ 3 DMF (3 ). An unexpected mixed oxidation state network with a composition of [Mn II 4 Mn III 16 O10 (OH)6 (OCH3 )24 (TCNQF4 )2 ](NO3 )2 ⋅ 24 CH3 OH (4 ), is formed if Mn(NO3 )2 ⋅ x  H2 O is used in place of Mn(BF4 )2 ⋅ x  H2 O in the reaction that leads to the formation of3 . Compounds1 –3 have been characterised by X‐ray crystallography; FTIR, Raman and UV/Vis spectroscopy; and electrochemistry. Compound4 has only been analysed by X‐ray crystallography and vibrational spectroscopy (Raman, FTIR), owing to rapid deterioration of the compound upon exposure to air. These results indicate that relatively minor changes in reaction conditions have the potential to yield products with vastly different structures. Compound1 adopts an anionic 2D network with unusual π‐stacked dimers of the TCNQF4 2− dianion, whereas2 and3 are composed of similar neutral sheets of [Mn(TCNQF4 )(DMF)2 ]. Interestingly, the solvent has a significant influence on the stacking of the sheets in the structures of2 and3 . In compound4, clusters with a composition of [Mn II 4 Mn III 16 O10 (OH)6 (OCH3 )24 (CH3 OH)4 ] 6+ serve as eight‐connecting nodes, whereas TCNQF4 2− ligands act as four‐connecting nodes in a 3D network that has the same topology as fluorite. Compound3 exhibits an exceptionally high super‐catalytic activity for the electron‐transfer reaction between ferricyanide and thiosulfate ions in aqueous media. Abstract : Predicting the unpredictable : Minor changes to reaction conditions with Mn(BF4 )2 ⋅ x  H2 O and 2, 3, 5, 6‐tetrafluoro‐7, 7, 8, 8‐tetracyanoquinodimethane (TCNQF4 ) result in four new compounds; all of which have been characterized by means of X‐ray crystallography to reveal very different structures, including a Mn20 cluster (see figure). One of these compounds also exhibits supercatalytic activity for an electron‐transfer reaction in aqueous media.